2021
DOI: 10.1186/s13568-021-01310-9
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between clarithromycin resistance, virulence factors and clinical characteristics of the disease in Helicobacter pylori infected patients in Shahrekord, Southwest Iran

Abstract: The purpose of this study was to determine the mutations associated with clarithromycin resistance in Helicobacter pylori strains isolated from biopsy samples that were collected from the endoscopic ward of Shahrekord Hajar teaching Hospital and also to study the frequency of virulence factor and their correlation and pathological findings with clarithromycin resistance during the years 2019–2020. In this cross-sectional descriptive study, 152 patients with Helicobacter pylori infection were considered, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…We may suggest that H. pylori strains carrying mutations in the 23S RNA subunit conferring clarithromycin resistance may develop an intense inflammatory response in the gastric epithelial cells and, thus, can proliferate more rapidly, possibly causing diarrhea, halitosis, or abdominal pain in the 5–18-year-old group. It was reported that most people with mild chronic inflammation have H. pylori strains without mutations, and most people with moderate to severe inflammation have mutant (A2142G and A2143G point mutations) H. pylori strains in a very recent 2021 study [ 50 ], which supports our hypothesis. The low sensitivity of stool PCR for detecting H. pylori infection compared with HpSA in children was previously solved via HpSA to detect H. pylori -positive samples.…”
Section: Discussionsupporting
confidence: 88%
“…We may suggest that H. pylori strains carrying mutations in the 23S RNA subunit conferring clarithromycin resistance may develop an intense inflammatory response in the gastric epithelial cells and, thus, can proliferate more rapidly, possibly causing diarrhea, halitosis, or abdominal pain in the 5–18-year-old group. It was reported that most people with mild chronic inflammation have H. pylori strains without mutations, and most people with moderate to severe inflammation have mutant (A2142G and A2143G point mutations) H. pylori strains in a very recent 2021 study [ 50 ], which supports our hypothesis. The low sensitivity of stool PCR for detecting H. pylori infection compared with HpSA in children was previously solved via HpSA to detect H. pylori -positive samples.…”
Section: Discussionsupporting
confidence: 88%
“…The interplay between virulence and antibiotic resistance is documented – for example, Pseudomonas aeruginosa with oprD mutants that impart carbapenem resistance were also more virulent (Geisinger and Isberg, 2017). The H. pylori strains with virulence genes oipA, vacA , and iceA1 were resistant to clarithromycin (Hosseini et al, 2021). On the contrary, there might also be a trade-off between the two – less virulent ( cagA -negative) strains of H. pylori were found to be clarithromycin resistance (Brennan et al, 2018) and vice versa (da Silva Benigno et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The Spearman’s rank correlation, which is less sensitive to outliers, was used to examine the relationship between the numbers of antibiotic resistance genes and virulence genes. The significance of the correlation coefficient was tested using cor.test (which is based on t-distribution or approximation) in R. As the extent of antibiotic resistance is also associated with the differential presence of virulence genes, in particular cytotoxin-associated genes (cags) (Brennan et al, 2018; da Silva Benigno et al, 2022; Hosseini et al, 2021; Liu et al, 2022), to further understand their interplay, genomes were grouped based on cags into three categories namely “all cags” when all cags were present, “ cag2- ” when only cag2 was missing, and “others” when most of the cags including cag2 and cagA were missing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As for the high prevalence of the bacterium and its related diseases, proper treatment is very important. Today, standard treatment is a three-stage drug that consists of an acid neutralizer and two antibiotics, clarithromycin (CLA), and amoxicillin or metronidazole for 14 days ( Hosseini et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%